Iowa CBC reporting form, Eldora, December 29, 1985 - Sommerlot, Ramona R.et al (1985)
Checklist dated December 29, 1985 compiled by Ramona Sommerlot. A list of birds sighted by Sommerlot and eleven others around Eldora. A total of 38 species and 2,608 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed